EPA negotiations between the EU and SADC/SACU grouping: partnership or asymmetry? - Van der Holst, Marieke (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (Political Science. International Studies))--University of Stellenbosch, 2009.